Effectiveness of stories in developing the environmental awareness of the kindergarten child in Hafar Al-Batin governorate - Al-Anzi, Hanan Matir Suhman (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to know Effectiveness of stories in developing the environmental awareness of the kindergarten child in Hafar al-Batin governorate in (air, water, food, plants, animals, sounds). This is because these aspects are of great importance in the lives of children in general and the kindergarten child in particular. Based on taking the opinions of specialists and the exploratory study, as well as previous studies, the illustrated stories, then with their elements and ingredients have the ability to attract the child towards them. And among these elements: pictures and drawings, beautiful bright colors and good output, luxurious printing, and other elements can capture the heart and mind of the child, as well as these elements makes storyboards unique literature compare with types of children's literature. Therefore, the researcher prepared the illustrated environmental awareness scale in order to develop positive environmental behaviors in the kindergarten child, which was used with (30) boys and girls between the ages of (4-5) years. The researcher used the quasi-experimental approach with one group (pre and post application). The results revealed that there were statistically significant differences at the level of significance (0.01) between the mean scores of the sample members on the environmental awareness scale before and after the application of the proposed narrative program in favor of the post application. In light of the results of the study, the researcher recommended the following: Planning activities in the kindergarten to develop environmental awareness, providing appropriate modern learning resources for children that address the most important environmental issues and problems and other recommendations.
Keywords: storyboards; environmental awareness; kindergarten child